2006
DOI: 10.1007/s00521-006-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the main patterns of natural time series for long-term neurofuzzy prediction

Abstract: A combination of singular spectrum analysis and locally linear neurofuzzy modeling technique is proposed to make accurate long-term prediction of natural phenomena. The principal components (PCs) obtained from spectral analysis have narrow band frequency spectra and definite linear or nonlinear trends and periodic patterns; hence they are predictable in large prediction horizon. The incremental learning algorithm initiates a model for each of the components as an optimal linear least squares estimation, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The method has also shown its effectiveness in the long term prediction of the sunspot number time series (Gholipour et al, 2005). The use of singular spectral analysis results in the identification and separation of the main components with different periodicities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method has also shown its effectiveness in the long term prediction of the sunspot number time series (Gholipour et al, 2005). The use of singular spectral analysis results in the identification and separation of the main components with different periodicities.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the utilization of SSA indirectly amounts to using external information about the behavior of the time series in the previous cycles as well. Therein lies the secret of the success in longer term prediction (Loskutov et al, 2001a, b;Gholipour et al, 2005). We seem to be doing the impossible by predicting multi-steps ahead by using only a few hours' past data; but we are, in fact, indirectly using other data on periodicities of the time series obtained through consideration of much longer term past values that could not have been directly used in prediction tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, modern space weather forecasters rely on a great variety of forecast systems, ranging from simple nonlinear models to complex informationbased (empirical approaches) physical, and hybrid models (Bothmer and Daglis, 2007). Over the last two decades, which was when real-time data began to be available online, data-driven approaches, such as artificial neural networks (Bothmer and Daglis, 2007), neurofuzzy modeling (Gholipour et al, 2005(Gholipour et al, , 2007, Kalman filtering (Bothmer and Daglis, 2007), among others, have been shown to perform well in space weather forecasting. Space weather forecasting can be classified into five classes according to the forecasting frame-time:…”
Section: Problem Statementmentioning
confidence: 99%
“…It is shown that the cyclic solar activity has chaotic characteristics especially during storm time which depicts the difficulties in long-term prediction of solar activity indices (Stefanski, 2003;Gholipour et al, 2007;Mirmomeni et al, 2007). It has to be said that, deterministic chaos appears in different fields of science like physics, biomedicine, and engineering (Ruelle, 1978;Kocarev et al, 2006).…”
Section: Introductionmentioning
confidence: 99%